ANALISIS HUBUNGAN PENDAPATAN WISATAWAN DAN HARGA PARIWISATA TERHADAP PERMINTAAN PARIWISATA DENGAN VECM - SIANIPAR, MERARY; SUCIPTAWATI, NI LUH PUTU; DHARMAWAN, KOMANG (E-Jurnal Matematika; Vol 5 No 2 (2016)DO - 10.24843/MTK.2016.v05.i02.p120, 2016)
Tourism demand is focused on estimating variables which influence tourist visit. The tourism demand that we discuss on this research is the tourism demand to Bali of the major tourism-generating country was Australia. The aim of this research is to analyze the relationship between tourist income and tourism price to tourism demand using VECM . VECM requires that the variables in the model must be stationary and fulfilled a cointegration condition. In order to make it valid, the stationarity of variables in the model have to be checked using ADF unit root test. In additon, cointegration between these variables are examined using Johansen’s cointegration test. The results of ADF unit root test show that indicated the tourist income, the tourism price and the tourism demand for Australia data are stationary in first lag or I(1). Cointegration test shows that all variables are cointegrated, i.e. have a long-run relationship. In the long-run, the tourist income and tourism price give positive effect to the tourism demand. This means, the increase of tourist income and tourism price will contribute to the increase in tourism demand. In addition, in the short-run, the tourist income and the tourism price give negative effect to the tourism demand. This means, the increase of tourist income and tourism price will contribute to the decrease in tourism demand.
Keywords: ADF Unit Root Test, Johansen’s Cointegration Test, The Tourism Demand, The Tourist Income, The Tourism Price, Vector Error Correction Model